Meningkatkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun Melalui Bermain Lempar Bola Kreweng di TK Negeri Pembina 1 Mojosari - Lestari Aprilianti; Sri Setyowati (Departement of Mathematics Education, 2023)
Early childhood children need to be provided with age-appropriate and ability-appropriate stimulation, and one aspect that needs to be developed is gross motor skills. The purpose of this study is to improve gross motor skills using the activity of playing